Si-Ni-San alleviates early life stress-induced depression-like behaviors in adolescence via modulating Rac1 activity and associated spine plasticity in the nucleus accumbens - Ye, Lihong; Wu, Jiayi; Liu, Zuyi; Deng, Di; Bai, Shasha; Yang, Lei; Xuan, Yao; Liu, Zehao; Shi, Yafei; Liu, Zhongqiu; Zhang, Rong; Zhao, Jinlan (Frontiers in Pharmacology, 2023)
Background: Early life stress (ELS) is a major risk factor for depression in adolescents. The nucleus accumbens (NAc) is a key center of the reward system, and spine remodeling in the NAc contributes to the development of depression. The Si-Ni-San formula (SNS) is a fundamental prescription for treating depression in traditional Chinese medicine. However, little is known about the effects of SNS on behavioral abnormalities and spine plasticity in the NAc induced by ELS. Purpose: This study aimed to investigate the therapeutic effect and the modulatory mechanism of SNS on abnormal behaviors and spine plasticity in the NAc caused by ELS. Methods: We utilized a model of ELS that involved maternal separation with early weaning to explore the protective effects of SNS on adolescent depression. Depressive-like behaviors were evaluated by the sucrose preference test, the tail suspension test, and the forced swimming test; anxiety-like behaviors were monitored by the open field test and the elevated plus maze. A laser scanning confocal microscope was used to analyze dendritic spine remodeling in the NAc. The activity of Rac1 was detected by pull-down and Western blot tests. Viral-mediated gene transfer of Rac1 was used to investigate its role in ELS-induced depression-like behaviors in adolescence. Results: ELS induced depression-like behaviors but not anxiety-like behaviors in adolescent mice, accompanied by an increase in stubby spine density, a decrease in mushroom spine density, and decreased Rac1 activity in the NAc. Overexpression of constitutively active Rac1 in the NAc reversed depression-related behaviors, leading to a decrease in stubby spine density and an increase in mushroom spine density. Moreover, SNS attenuated depression-like behavior in adolescent mice and counteracted the spine abnormalities in the NAc induced by ELS. Additionally, SNS increased NAc Rac1 activity, and the inhibition of Rac1 activity weakened the antidepressant effect of SNS. Conclusion: These results suggest that SNS may exert its antidepressant effects by modulating Rac1 activity and associated spine plasticity in the NAc.